Prospective Trial of a Novel Nomogram to Achieve Updated Vancomycin Trough Concentrations. (12th September 2013) - Wesner, Amber R.; Brackbill, Marcia L.; Coyle, Larissa L.; Kidd, Robert S.
Abstract : Purpose . To determine if the use of a novel vancomycin nomogram predicts dosing regimens that achieve target trough concentrations equal to or more accurate than dosing regimens calculated using traditional pharmacokinetic calculations, evaluate the incidence of subtherapeutic and supratherapeutic troughs, and assess pharmacist's impressions of the nomogram. Methods . Prospective, open-label study in 473 patients who had a new order for vancomycin and were >18 years of age and ≤120 kg. Patients were randomized to the active group, dosed using the nomogram, or to the control group, dosed using traditional pharmacokinetic calculations already in place at our institution. Results . Patients dosed via nomogram were within the appropriate trough range in 44% of cases compared to 33% in the control group (P = 0.014 ). Vancomycin troughs less than 10 mcg/mL were significantly decreased with the use of nomogram (P = 0.032 ). Incidence of supratherapeutic troughs, greater than 20 mcg/mL, was not significantly different between groups (P = 0.706 ), and pharmacists agreed that the nomogram was easy to use and saved their time. Conclusions . A novel vancomycin nomogram was prospectively validated and found to be more effective than traditional pharmacokinetic dosing. The nomogram is being implemented as the standard dosing protocol at our institution.